PENGARUH WORKING CAPITAL TURNOVER, CASH TURNOVER, INVENTORY TURNOVER DAN CURRENT RATIO TERHADAP PROFITABILITAS (ROA) PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI - Natania, Clarissa -; Vani, Gracia Chou; Budiman, Felicia Alma; Meiden, Carmel - (Makro Jurnal Manajemen Dan Kewirausahaan, 2023)
The purpose of this study is to provide an overview of the relevance of the value of accounting information to working capital. This research uses a systematic literature review (SLR). methodological approach to identify, study, evaluate, and interpret all available research with relevant researchquestions. To search for journals related to the research topic, researchers use search keywords : “working capital turnover”, “cash turnover”, “inventory turnover”, “current ratio” and “profitability (ROA). This study discusses important aspects of research such as researchtopics, research methods, and theories used in 30 published literature reviews that were collected during the research period from 2017 2022. Based on a systematic literature review, it shows a significant development of value relevance research in terms of the number, diversity of theories, methods, and attention of studies during the period 2017-2022.